Pardon the Interruption: A Modification of Fischer’s Venerable Reaction for the Synthesis of Heterocycles and Natural Products - Susick, Robert B.; Morrill, Lucas A.; Picazo, Elias; Garg, Neil K. (Synlett, 2017)
This account provides an overview of our laboratory’s studies of an unusual variant of the Fischer indolization reaction. We describe the discovery of the so-called ‘interrupted Fischer indolization’ and the development of the reaction from a methodological standpoint. In addition, our efforts to evaluate and apply this methodology in the context of akuammiline alkaloid total synthesis are discussed.1 Introduction2 Interrupted Fischer Indolization Methodology3 Applications in Akuammiline Alkaloid Total Synthesis4 Concluding Thoughts
Keywords: total synthesis; alkaloids; heterocycles; natural products; akuammilines; indolines; indoles; Fischer indolization